Kebijakan Hukum Pidana Dalam Perlindungan Pekerja Rumah Tangga Korban Kekerasan - Siti Rahmawati (Universitas Islam Indonesia, 2020)
In the employment sector, Domestic Workers (PRT, housemaids) are not categorized as formal occuparion. Therefore, domestic workers are included in the informal sector. These domestic workers in the informal sector are vulnerable to various acts of violence, hence are in dire need of extra protection from the state. This normative legal research concludes that the legal policies provided by the government in protecting domestic workers are in the form of providing restitution and compensation, counseling, medical services/assistance, legal assistance, and providing information. The policy is contained in Law Np. 23 of 2004 on the Elimination of Domestic Violence and Law No. 31 of 2014 on the Amendments to Law No. 13 of 2006 on the Protection of Witnesses and Victims. In addition, the role of government officials is very important for the implementation of legal protection for domestic workers. The role of the apparatus in providing protection to domestic workers victims of violence is regulated in the Law of the Republic of Indonesia No. 23 of 2004 concerning the Elimination of Domestic Violence